Mikrokontroler untuk Mengukur Kecepatan Kereta Api sebagai Sumber Belajar Mahasiswa Fisika - Imas Ratna Ermawati; Martin Martin; Tri Isti Hartini; Sugianto Arjo; Supriyatna Supriyatna; Reza Annisa Salsabilla (TIME in Physics, 2023)
The simulation of uniform straight motion using a miniature train based on the Arduino Uno has been carried out to determine velocity through a complex number approach. The experiment was conducted repeatedly at the same distance to obtain a constant velocity. The equation used to determine the velocity of the train is the application of complex number a + ib with the function  in variation of power. The results show that the velocity of the trains obtained has the same value, thus proving that the uniform straight motion is valid with the same acceleration which is zero (a=0) in this experiment.